Doped ferric sodium pyrophosphate material as well as preparation method and application thereof

Through co-precipitation grinding and freeze-drying treatment, the problem of uneven doping of sodium ferrophosphate phosphate material is solved, and the preparation of high-purity doped sodium ferrophosphate phosphate material is realized, which improves the electrochemical performance and crystal structure stability of the positive electrode material of sodium ion battery.

CN120364666APending Publication Date: 2025-07-25SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI

Patent Information

Application Number
CN202510455149.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The uneven doping of existing sodium ferric pyrophosphate materials leads to less obvious improvement in electrochemical performance and unstable crystal structure, affecting battery performance.

Method used

By co-precipitation grinding and freeze-drying treatment, atomic-level doped ferrous phosphate intermediate is formed by controlling the co-precipitation reaction of pH 4.5 to 5.5, and a high-purity doped sodium ferrous phosphate phosphate material is formed under the action of organic reducing carbon source.

Benefits of technology

The uniform distribution of doped elements and the high compaction density of the material are achieved, the electrochemical performance and crystal structure stability are improved, and the electrochemical performance of the positive electrode material of sodium ion battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364666A_ABST
    Figure CN120364666A_ABST
Patent Text Reader

Abstract

The invention provides a doped ferric sodium pyrophosphate material as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, blending ferrite, phosphate, strong acid and an antioxidant to form a solution A; s2, adding doped metal salt, sodium salt and a chelating agent into the solution A to form a solution B; s3, co-dropwise adding the solution B and the coprecipitation solution into grinding equipment, and maintaining the pH value to be 4.5-5.5 in the grinding process; s4, mixing and stirring the reaction product and water to form a suspension, and freeze-drying to obtain a precursor material; and S5, mixing the precursor material with a carbon source, and performing high-temperature heat treatment to obtain the doped ferric sodium pyrophosphate material. The material has excellent electrochemical performance, high compaction density and regular product morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium-ion batteries, and particularly relates to a doped sodium iron pyrophosphate material, a preparation method thereof, and an application thereof. Background Art

[0002] Sodium iron pyrophosphate has a stable structure, which is beneficial to the insertion and extraction of sodium ions. It has a high specific capacity, good rate performance, and can maintain the stability of the structure well during the electrochemical process, making it a good choice as a cathode material for sodium-ion batteries.

[0003] Due to the poor electronic conductivity of the sodium iron pyrophosphate material, ion doping is often required to improve its internal conductivity. CN117577830A discloses a preparation method of a sodium manganese iron pyrophosphate material, which includes performing a co-precipitation reaction by adding a manganese salt solution, a phosphorus source solution, and an ammonia water solution in a co-current manner, and simultaneously introducing an iron salt solution into the manganese salt solution in a continuous flow manner to form a phosphate precursor nucleus; after the manganese salt solution is consumed, the remaining iron salt solution continues to perform a co-precipitation reaction with the phosphorus source solution and the ammonia water solution to form an iron phosphate layer outside the phosphate precursor nucleus, and then aging to obtain precursor particles. Thus, the content of manganese element in the inner core of the obtained sodium manganese iron pyrophosphate decreases in a gradient manner and the content of iron element increases in a gradient manner.

[0004] CN117923452A discloses a method for preparing a composite sodium iron pyrophosphate material. The sodium iron pyrophosphate material is prepared by a two-step method. First, a precursor is prepared by a co-precipitation method, and element doping is added during the preparation of the precursor. The molar ratio of (Fe + M):(PO4) in the precursor is 3:4. By introducing a sodium source through a solid-phase method, a batch preparation of a multi-doped sodium iron pyrophosphate material can be realized.

[0005] CN118062822A discloses a preparation method of a sodium iron pyrophosphate derivative, which includes: dissolving an iron source, a first phosphorus source, and a doping ion source containing a doping element in deionized water, mixing and adjusting the pH value to 1.5 - 4.5, so that iron ions, phosphate ions, and doping element ions co-precipitate in deionized water to obtain a solid precursor; mixing and sintering the precursor with a sodium source, a manganese source, and a second phosphorus source to obtain a sodium iron pyrophosphate derivative doped with the doping element ions.

[0006] Conventional doping methods are prone to uneven distribution of local iron ions and doping ions, resulting in uneven doping of the internal crystal structure, and the improvement of electrochemical performance is not obvious. Even the enrichment of iron ions is accompanied by the generation of electrochemically inert phases, seriously affecting the electrochemical performance of the material. Summary of the Invention

[0007] The object of the present invention is to provide a sodium iron pyrophosphate phosphate material with uniform doping and stable phase structure, which has excellent electrochemical performance, high tap density and regular product morphology. To this end, the present invention provides the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a sodium iron pyrophosphate phosphate material, comprising the following steps:

[0009] S1. Mix a ferrous salt, a phosphate, a strong acid and an antioxidant to form a solution A;

[0010] S2. Add a doping metal salt, a sodium salt and a chelating agent to the solution A to form a solution B;

[0011] S3. Co-drip the solution B and a co-precipitation solution into a grinding device, and maintain the pH value during the grinding process at 4.5-5.5;

[0012] S4. Mix the product after the reaction is completed with water and stir to form a suspension, and obtain a precursor material after freeze-drying;

[0013] S5. Mix the precursor material with a carbon source and perform high-temperature heat treatment to obtain the doped sodium iron pyrophosphate phosphate material.

[0014] When the present invention prepares the doped sodium iron pyrophosphate phosphate material, firstly, an atomically doped ferrous phosphate intermediate is prepared through a co-precipitation grinding and freeze-drying process. Sodium is incorporated through the intermediate, and under the action of an organic reducing carbon source, a high-purity doped sodium iron pyrophosphate phosphate material can be formed in one step, which shows good electrochemical performance as a cathode material for sodium-ion batteries.

[0015] Further, in step S1, the molar ratio of ferrous ions to phosphate ions in the solution A is (0.3-1.4):1.

[0016] In a specific embodiment of the present invention, the molar ratio of ferrous ions to phosphate ions in the solution A is 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, etc.

[0017] Further, in step S1, the pH value of the solution A is 0.5-1.0. The addition of a strong acid can ensure that the pH of the solution A is below 1.0. If the pH value is too high, precipitation will occur, resulting in non-uniform products.

[0018] In a specific embodiment of the present invention, the pH value of the solution A is 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0.

[0019] Further, in step S1, the strong acid is one or more of hydrochloric acid and sulfuric acid.

[0020] Further, in step S1, the molar amount of the antioxidant in solution A is 1-3% of the total molar amount of the ferrous salt and the phosphate; preferably, the molar amount of the antioxidant in solution A is 1.5-2% of the total molar amount of the ferrous salt and the phosphate.

[0021] In a specific embodiment of the present invention, the molar amount of the antioxidant in solution A is 1%, 1.2%, 1.5%, 1.55%, 1.67%, 1.8%, 2%, 2.5%, 3%, etc. of the total molar amount of the ferrous salt and the phosphate.

[0022] Further, in step S1, the ferrous salt is one or more of ferrous sulfate, ferrous chloride, ferrous oxalate, and ferrous acetate.

[0023] Further, in step S1, the phosphate is one or more of monoammonium phosphate, diammonium phosphate, and ammonium phosphate.

[0024] Further, in step S1, the antioxidant is one or more of ascorbic acid and sodium borohydride. The addition of the antioxidant can prevent the oxidation of ferrous ions.

[0025] Further, in step S2, the doped metal salt is one or more of soluble manganese, titanium, magnesium, vanadium, nickel, cobalt, and copper salts.

[0026] Preferably, the doped metal salt is one or more of manganese chloride, manganese nitrate, and manganese sulfate.

[0027] Further, in step S2, the sodium salt is one or more of sodium carbonate, sodium phosphate, and sodium hydroxide.

[0028] Further, in step S2, the molar ratio of ferrous ions to doped metal ions in solution B is 1:(0.007-0.04). The amount of doped metal ions cannot be too high, otherwise it will cause a change in the crystal phase.

[0029] In a specific embodiment of the present invention, the molar ratio of ferrous ions to doped metal ions in solution B is 1:0.007, 1:0.01, 1:0.02, 1:0.03, 1:0.04, etc.

[0030] Further, in step S2, the molar amount of sodium ions is 1.3-1.5 times the total molar amount of ferrous ions and doped metal ions.

[0031] In a specific embodiment of the present invention, the molar amount of the sodium ions is 1.3 times, 1.35 times, 1.4 times, 1.45 times or 1.5 times the total molar amount of the ferrous ions and the doped metal ions.

[0032] Further, in step S2, the chelating agent is one or more of citric acid, Ethylene Diamine Tetraacetic Acid (EDTA), ascorbic acid, and Hexadecyl trimethylammonium Bromide (CTAB).

[0033] Further, in step S2, the addition amount of the chelating agent is 1-4% of the total molar amount of the raw materials. Herein, the "raw materials" include ferrous salts, phosphates, antioxidants, doped metal salts, and sodium salts.

[0034] Further, in step S3, the coprecipitation solution is ammonia water.

[0035] Furthermore, in step S3, the coprecipitation solution is an ammonia water solution with a mass concentration of 5-10%.

[0036] Further, in step S3, the grinding equipment is equipment having the function of grinding the product fine, such as: sand mill, wet planetary ball mill, wet vibration ball mill, etc., whereby the final product particle size can be controlled between 300-400 nm.

[0037] Further, in step S3, the grinding equipment is a sand mill, the sand grinding speed is 1500-2500 rpm, and the sand grinding time is 20-60 min.

[0038] Further, in step S3, a dilute acid is used as the bottom liquid in the grinding equipment to maintain the pH value during the grinding process between 4.5-5.5.

[0039] Preferably, the dilute acid is a hydrochloric acid solution.

[0040] In a specific embodiment of the present invention, in step S3, the pH value during the grinding process is 4.5, 5.0, 5.5 or any value between 4.5-5.5.

[0041] In step S3, the reaction process continuously consumes hydrogen ions, causing the pH value of the system to increase. In different pH ranges, the reaction products will be different. Therefore, it is very important to maintain the constant pH value during the reaction process. The introduction of ammonia water, on the one hand, serves as a precipitating agent for the reaction, and on the other hand, cooperates with the acid in the system to form a pH buffer solution to maintain the constant pH value during the reaction process.

[0042] Further, in step S3, after the reaction is completed, the solution is filtered by suction, and the solid phase is washed. When the ionic conductivity of the washing liquid is reduced to less than 0.1 S / cm, the product is obtained.

[0043] Further, in step S4, the specific parameters of the freeze-drying are freeze-drying at -25 to -15 °C for 3 to 5 h to obtain the precursor material.

[0044] In a specific embodiment of the present invention, the temperature of the freeze-drying is -25 °C, -24 °C, -23 °C, -22 °C, -21 °C, -20 °C, -19 °C, -18 °C, -17 °C, -16 °C, -15 °C, etc.

[0045] In a specific embodiment of the present invention, the time of the freeze-drying is 3 h, 3.5 h, 3.6 h, 3.8 h, 4 h, 4.3 h, 4.5 h, 4.6 h, 4.8 h, 5 h, etc.

[0046] Further, in step S5, the carbon source is one or more of glucose, sucrose, PEG-2000, polyacrylamide (PAM), carbon nanotubes, graphene oxide, citric acid, and ascorbic acid.

[0047] Further, in step S5, the dosage of the carbon source is 3 to 4% of the total mass of the raw materials; wherein, the "raw materials" include ferrous salts, phosphates, antioxidants, doped metal salts, sodium salts, and chelating agents.

[0048] Further, in step S5, the high-temperature heat treatment temperature is 450 to 550 °C, and the heat treatment time is 4 to 10 h.

[0049] In a specific embodiment of the present invention, the high-temperature heat treatment temperature is 450 °C, 460 °C, 480 °C, 500 °C, 520 °C, 550 °C, or any value between 450 and 550 °C.

[0050] In a specific embodiment of the present invention, the high-temperature heat treatment time is 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or any value between 4 and 10 h.

[0051] On the other hand, the present invention provides a doped sodium iron pyrophosphate phosphate, which is obtained by the above preparation method.

[0052] In a third aspect, the present invention provides the application of the above-mentioned doped sodium iron pyrophosphate phosphate in the field of positive electrode materials for sodium ion batteries.

[0053] Compared with the prior art, the beneficial effects brought by the technical solution of the present invention are as follows:

[0054] (1) In step S1 of the present invention, a slight precipitate will form in solution A. Adding sodium salt in step S2 can embed sodium into the material, making the product crystal phase more stable. If the sodium salt is added in step S1, when the iron phosphate material has not been formed yet, sodium will hinder the formation of the material and will not embed into the material. Instead, it will attach more to the surface of the material, resulting in an unstable crystal phase structure.

[0055] (2) Conventional co-dripping easily forms products in the micron scale. The present invention adopts a co-precipitation grinding process, and nano-scale products are continuously formed during the reaction process. Moreover, the product morphology is regular and the compaction density is higher.

[0056] (3) In step S3 of the present invention, solution B easily forms a precipitate when encountering ammonia water. Compared with the method of separately co-dripping the iron phosphate solution, doping solution, and co-precipitation solution, adopting the process of the present invention can make the distribution of doping elements more uniform.

[0057] (4) Freeze-drying can reduce the reaction energy during high-temperature heat treatment, making the reaction more complete, with fewer impurity phases and better crystallinity in the prepared material. Moreover, compared with other drying methods, freeze-drying causes less damage to the sample and can greatly reduce the damage of oxygen and water to the material during the drying process. On the other hand, the chelating agent can reduce the negative impact of freeze-drying on the product and act as a protective agent. The chelating agent can form hydrogen bonds with the active components and replace the position of water molecules, thereby providing protection during the dehydration process of freeze-drying.

[0058] (5) The present invention realizes the atomic-level doping of metal elements into sodium iron pyrophosphate phosphate. The precursor product is uniform, resulting in a relatively high purity of the doped sodium iron pyrophosphate phosphate, with less by-product generation. The prepared doped material has good electrochemical performance when used as the positive electrode of a sodium-ion battery. Description of the Drawings

[0059] Figure 1 SEM morphology diagram of the doped sodium iron pyrophosphate phosphate material obtained in Example 1;

[0060] Figure 2 XRD pattern of the doped sodium iron pyrophosphate phosphate material obtained in Example 1;

[0061] Figure 3 Electrical performance test diagram of the sodium-ion battery obtained in Example 1;

[0062] Figure 4 SEM morphology diagram of the sodium iron pyrophosphate phosphate material obtained in Comparative Example 1. Detailed Embodiments

[0063] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clear and understandable, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0064] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0065] It should be noted that in this article, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Without further limitation, the element defined by the statement "including one..." does not exclude the existence of additional identical elements in the process, method, article or device including the said element.

[0066] The present invention will be further described in detail below through specific embodiments.

[0067] Example 1

[0068] Preparation of doped sodium iron pyrophosphate phosphate material:

[0069] Add 1 mol of ammonium dihydrogen phosphate, 0.3 mol of ferrous chloride, 500 mL of hydrochloric acid and 0.02 mol of ascorbic acid to 2000 mL of pure aqueous solution to prepare phosphorus-iron mixed solution A;

[0070] Add 0.01 mol of manganese chloride, 0.42 mol of sodium carbonate and 0.02 mol of citric acid to the mixed solution A to form solution B;

[0071] Add hydrochloric acid to 500 mL of ultrapure water, and then add it to a sand mill to form a bottom liquid with a pH of 5.0. Drop solution B and 8% wt ammonia water into the sand mill in a co-dropping manner, and monitor the pH with a pH meter to ensure that the pH is stable at 5.0. The sanding parameters are 2200 rpm. After sanding for 20 minutes, take out the product, filter and wash it four times to ensure that the ionic conductivity of the final washing filtrate is less than 1.0 S / cm to obtain a brown insoluble substance;

[0072] The above insoluble matter was added back into 1000 mL of ultrapure water and mixed and stirred to form a suspension, and a precursor material was obtained after freeze-drying at -10 °C for 3 h;

[0073] The above precursor material was ground and compounded with 0.02 mol of sucrose, and heat-treated at 500 °C for 9 h at a heating rate of 2 °C / min to obtain a doped sodium iron pyrophosphate phosphate material. Its SEM morphology is shown in Figure 1 as shown, and the XRD pattern is shown in Figure 2 as shown.

[0074] Preparation of sodium-ion battery:

[0075] The above doped sodium iron pyrophosphate phosphate, PVDF, and conductive carbon black were mixed evenly in a mass ratio of 90:5:5, NMP solvent was added, and after mixing and homogenizing, it was coated on carbon-containing aluminum foil. After drying in a blast oven at 80 °C, it was disassembled into small round pieces with a diameter of φ12 mm to obtain the positive electrode material of the sodium-ion battery; a metal sodium sheet was used as the negative electrode material; the electrolyte was DEC:EC at 1:1, and an additional 5% wt FEC was added as a protective agent, dissolved in LiPF6 organic reagent, and 40 μL of electrolyte was dropped in to assemble a sodium-ion battery.

[0076] The sodium-ion battery was tested for electrical performance. Under the test conditions of 0.1C, charge and discharge tests were carried out at 2.0 V to 4.0 V. The test results are shown in Figure 3 as shown.

[0077] Example 2

[0078] Preparation of doped sodium iron pyrophosphate phosphate material:

[0079] 2 mol of ammonium dihydrogen phosphate, 2.8 mol of ferrous chloride, 800 mL of hydrochloric acid, and 0.08 mol of ascorbic acid were added to 1500 mL of pure aqueous solution to prepare a phosphorus-iron mixed solution A;

[0080] 0.02 mol of manganese chloride, 4.05 mol of sodium carbonate, and 0.3 mol of ascorbic acid were added to the mixed solution A to form a solution B;

[0081] Hydrochloric acid was added to 1000 mL of ultrapure water and then added to a sand mill to form a bottom liquid with a pH of 5.0. Solution B and 5% wt ammonia water solution were added dropwise to the sand mill in a co-dropping manner, and the pH was monitored with a pH meter to ensure that the pH was stable at 5.0. The sanding parameters were 1500 rpm. After sanding for 50 min, the product was taken out, and suction filtration and washing were carried out four times to ensure that the ionic conductivity of the final washing filtrate was less than 1.0 S / cm to obtain a brown insoluble matter;

[0082] The above insoluble matter was added back into 500 mL of ultrapure water and mixed and stirred to form a suspension, and a precursor material was obtained after freeze-drying at -15 °C for 5 h;

[0083] The above precursor material is ground and compounded with 0.02 mol of PEG-2000, heated to 550 °C at a rate of 2 °C / min for heat treatment for 7 h, and a doped sodium iron pyrophosphate material is obtained.

[0084] The sodium-ion battery is prepared in the same manner as in Example 1.

[0085] Example 3

[0086] The difference between this example and Example 1 is that the metal doping substance is different, nickel chloride is used instead of manganese chloride, and the rest of the operations remain unchanged.

[0087] Example 4

[0088] The difference between this example and Example 1 is that the chelating agent is CTAB and the pH value of sand grinding is 5.5, and the rest of the operations remain unchanged.

[0089] Comparative Example 1

[0090] The difference between this comparative example and Example 1 is that the chelating agent citric acid is not added, and the rest of the operations remain unchanged. A sodium iron pyrophosphate material is prepared, and its SEM morphology diagram is as Figure 4 shown. Comparing Figure 1 and Figure 4 , it can be seen that the integrity of the doped sodium iron pyrophosphate material in Example 1 (i.e., Figure 1 ) is better, while the sodium iron pyrophosphate material in Comparative Example 1 (i.e., Figure 4 ) is mostly broken particles.

[0091] Comparative Example 2

[0092] The difference between this comparative example and Example 1 is that spray drying is used instead of freeze drying, and the rest of the operations remain unchanged. The spray drying conditions are as follows: the suspension is sprayed at 200 °C to obtain a powder, and then heated to 350 °C at a rate of 2 °C / min under nitrogen conditions for heat treatment for 6 h to obtain a precursor material.

[0093] Comparative Example 3

[0094] The difference between this comparative example and Example 1 is that the co-dripping method is not used, solution B is directly mixed with ammonia water for coprecipitation reaction, and then the obtained precipitate is ground, and the rest of the operations are the same as in Example 1.

[0095] Comparative Example 4

[0096] The difference between this comparative example and Example 1 is that all raw materials (ammonium dihydrogen phosphate, ferrous chloride, hydrochloric acid, ascorbic acid, manganese chloride, sodium carbonate, citric acid) are mixed together, and then co-dripped into a sand mill with an ammonia water solution, and the rest of the operations are the same as in Example 1.

[0097] The sodium-ion batteries obtained from the above-mentioned examples and comparative examples were respectively subjected to the first charge-discharge test at a current density of 0.1C, and the results are shown in Table 1.

[0098] Table 1 Performance Tests of Examples and Comparative Examples

[0099]

[0100] As can be seen from Table 1, the sodium-ion batteries obtained from Examples 1 to 4 are superior to the sodium-ion batteries obtained from Comparative Examples 1 to 4 in terms of the three performance indicators of the first charge specific capacity, the first discharge specific capacity, and the first Coulombic efficiency. This is because no chelating agent was added in Comparative Example 1, resulting in a lack of protection during the freeze-drying process, leading to unstable crystal phases of the product and more broken particles. See Figure 4 ; in Comparative Example 2, conventional spray drying was used, resulting in more impurity phases in the product and reduced electrical performance; in Comparative Example 3, the coprecipitation grinding process was not adopted, resulting in uneven distribution of doping elements; in Comparative Example 4, the raw materials were not added step by step, and the presence of other raw materials would hinder the formation of the phosphoiron material, ultimately leading to unstable crystal phase structure of the material.

[0101] The specific embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0102] In addition, it should be noted that, in the case of no contradiction, the various specific technical features described in the above specific embodiments can be combined in any suitable manner. To avoid unnecessary repetition, the present invention will not separately describe various possible combination methods.

[0103] Furthermore, any combination can be made between various different embodiments of the present invention as long as it does not violate the idea of the present invention, and it should also be regarded as the content disclosed by the present invention.

Claims

1. A preparation method of a doped sodium iron pyrophosphate phosphate material, characterized in that, It includes the following steps: S1. Blend ferrous salt, phosphate, strong acid, and antioxidant to form solution A; S2. Add doped metal salt, sodium salt, and chelating agent to the said solution A to form solution B; S3. Co-drip the said solution B and co-precipitation solution into a grinding device, and maintain the pH value during the grinding process at 4.5 - 5.5; S4. Mix the product after the reaction is completed with water and stir to form a suspension, and obtain the precursor material after freeze-drying; S5. Mix the said precursor material with a carbon source and perform high-temperature heat treatment to obtain the doped sodium iron pyrophosphate phosphate material.

2. The preparation method according to claim 1, characterized in that, In step S1, the molar ratio of ferrous ions to phosphate ions in solution A is (0.3 - 1.4):1; The pH value of the said solution A is 0.5 - 1.0; The molar amount of antioxidant in the said solution A is 1 - 3% of the total molar amount of ferrous salt and phosphate; 3. The preparation method according to claim 1, characterized in that, In step S1, the said ferrous salt is one or more of ferrous sulfate, ferrous chloride, ferrous oxalate, ferrous acetate; The said phosphate is one or more of monoammonium phosphate, diammonium phosphate, ammonium phosphate; The said antioxidant is one or more of ascorbic acid, sodium borohydride; 4. The preparation method according to claim 1, characterized in that, In step S2, the said doped metal salt is one or more of soluble manganese, titanium, magnesium, vanadium, nickel, cobalt, copper salts; The said sodium salt is one or more of sodium carbonate, sodium phosphate, sodium hydroxide; In solution B, the molar ratio of ferrous ions to doped metal ions is 1:(0.007 - 0.04).

5. The preparation method according to claim 1, characterized in that, In step S2, the said chelating agent is one or more of citric acid, ethylenediaminetetraacetic acid, ascorbic acid, cetyltrimethylammonium bromide; The addition amount of the said chelating agent is 1 - 4% of the total molar amount of the raw materials.

6. The preparation method according to claim 1, characterized in that, In step S3, the said co-precipitation solution is ammonia water; The said grinding device is a sand mill, the sand grinding speed is 1500 - 2500 rpm, and the sand grinding time is 20 - 60 min; In the said grinding device, dilute acid is used as the bottom liquid to maintain the pH value during the grinding process.

7. The preparation method according to claim 1, characterized in that, In step S4, the specific parameters of the said freeze-drying are freeze-drying at -25 to -15 °C for 3 - 5 h.

8. The preparation method according to claim 1, wherein In step S5, the said carbon source is one or more of glucose, sucrose, PEG-2000, polyacrylamide, carbon nanotubes, graphene oxide, citric acid, ascorbic acid. The high-temperature heat treatment temperature is 450 - 550 °C, and the heat treatment time is 4 - 10 h.

9. The doped sodium iron pyrophosphate phosphate material prepared by the preparation method according to any one of claims 1 - 8.

10. Application of the doped sodium iron pyrophosphate phosphate material according to claim 9 in the field of positive electrode materials for sodium-ion batteries.

Citation Information

Patent Citations

  • Method for large-scale preparation of composite ferric sodium phosphate pyrophosphate material

    CN117923452A

Cited By

  • Titanium-doped NFPP positive electrode material, precursor thereof, preparation method of titanium-doped NFPP positive electrode material and sodium ion battery

    CN121553916A